Fatality Of Idiopathic Pulmonary Fibrosis due to Anonymous Root and Vague Features!!! - Rajagopalan, Dr. Balaji; Samuel, Dr.T.Rajini (South Eastern European Journal of Public Health, 2025)
The disease Idiopathic Pulmonary Fibrosis (IPF) also known as Cryptogenic Fibrosing Alveolitis has received global attention as this illness resulted in large number of deaths. It is characterized by the progressive decline in the lungs functions that are irreversible. The cause (root) of this illness is Unknown and this is the major setback for complete cure. Several risk factors such as Smoking , Gastric Esophageal Disease, Environmental hazards such as exposure to Gases, mud, coal, smoke ,stone dust, hay dust and Mold spores, silica, wood and metal dust, Genetic and Viral infections etc. can pave way for this dreadful disease after years of exposure. The clinical symptoms and signs are vague and non specific like dry cough aggravated on exertion, difficulty in breathing during exertion, Clubbing of the fingers and bilateral basal Crackles on auscultation. IPF occurs because of the aberrant wound healing processes involving abnormal and excessive collagen deposition in the pulmonary interstitium with inflammatory changes. The repetitive injuries in IPF occurs to the lung alveolar epithelial cells, the type 1 and type II cells , adjoining the alveolar surfaces .The diagnosis of this ailment is primarily clinical, including identifying potential risk factors such as exposure to inhalation pollutants. However, various evaluations like Chest Xray, CT Scan, Pulmonary Function tests, Biomarkers estimation and Lung biopsy can assist in confirming the diagnosis and Idiopathic Pulmonary Fibrosis(IPF) is a disease with no cure. Various supportive treatments like Medications, Oxygen Therapy, Breathing exercises to some extent delay the disease progression. A complete Cure of this ailment can reduce the definite mortality of these patients.